Perceived stress, social support, and insomnia in hemodialysis patients and their family caregivers: an actor-partner interdependence mediation model analysis - Tao, Yuxiu; Liu, Tongcun; Zhuang, Kaipeng; Fan, Lijuan; Hua, Yan; Ni, Chunping (Frontiers in Psychology, 2023)
Objectives: Patients' and caregivers' physical and mental health may interact. The theory of dyadic illness management holds that patients and caregivers should be regarded as a whole in health management. Previous studies have found that hemodialysis patients and their family caregivers experience poor sleep quality. Perceived stress and social support have effects on insomnia. However, the dyadic interaction between perceived stress, social support, and insomnia among hemodialysis patients and caregivers is unclear. This study aimed to explore the mediating role of social support in the association between perceived stress and insomnia in hemodialysis patient-caregiver dyads. Methods: A total of 259 hemodialysis patient-caregiver dyads completed the Chinese Perceived Stress Scales (CPSS), the Perceived Social Support Scale (PSSS), and the Athens Insomnia Scale (AIS) in Lanzhou, China, from May 2022 to July 2022. The actor-partner interdependence mediation model analysis was used for data analysis. Results: In the actor effect, there was a significant positive correlation between perceived stress and insomnia in hemodialysis patients (β = 0.091, P = 0.001) and their family caregivers (β = 0.588, P < 0.001). Patient's and caregiver's social support played partial mediating roles in the relationship between caregiver's perceived stress and insomnia (β = 0.135, P < 0.001 and β = 0.111, P < 0.001). In the partner effect, caregiver's perceived stress was positively connected with patient's insomnia (β = 0.915, P < 0.001), and the mediating effect of patient's social support on the relationship between caregiver's perceived stress and patient's insomnia was statistically significant (β = -0.040, P = 0.046).The perceived stress, social support and insomnia of hemodialysis patients and their family caregivers had interactive effects. Effective dyadic-based interventions should be developed to improve hemodialysis patients' and caregivers' sleep quality.